In vivo confocal scanning laser microscopy in patients with primary Sjögren's syndrome: A monocentric experience. Issue 4 (July 2015) - Gabbriellini, Giovanna; Baldini, Chiara; Varanini, Valentina; Notarstefano, Chiara; Pepe, Pasquale; Fanucci, Francesca; Ferro, Francesco; Luciano, Nicoletta; Mosca, Marta; Nardi, Marco; Bombardieri, Stefano
Abstract: Aims. (i) To analyze the in vivo corneal structure and sub-basal plexus nerves in patients with primary Sjögren's syndrome (pSS) and no-SS dry eye by confocal scanning laser microscopy (CSLM) and (ii) to correlate CSLM findings with tear function tests and with patients' subjective dryness. Methods. Seventeen patients with pSS, 16 no-SS dry eye, and 20 healthy volunteers were included. CSLM parameters taken into consideration included: basal epithelial integrity, corneal thickness, epithelial cellular density, keratocyte activation, and sub-basal plexus morphology. Statistical analysis was carried out using SPSS-13 (Chicago IL, USA). Results. CSLM pachymetric data and the superficial epithelium cell density were significantly lower in pSS versus no-SS dry eye ( p < 0.0001); keratocyte activation and sub-basal nerve abnormalities were also more frequent in pSS patients ( p < 0.0001). CSLM findings well correlated with both the ocular test results and the patients' perception of ocular dryness at the baseline and over the follow-up. Conclusion. CSLM might be a useful novel tool in the assessment of the involvement of the lachrymal functional unit in pSS.